Combining Spatial and temporal dynamic scheduling techniques on wireless vehicular communications - Silva, Luis
The Vehicular Time-Triggered Protocol (V-FTT) is an infra-structured communication protocol for vehicular communications, based on IEEE802.11p/ETSI ITS-G5 standards, that brings improved timeliness and determinism by taking advantage of cooperative roadside units interconnected by a backhauling network. In a previous work, the use of a Spatial TDMA framework (STDMA) to improve both coverage and communication reliability on V-FTT networks was proposed. A set of experiments, carried out in a real scenario, proved that STDMA brings coverage and reliability improvements but with limitations. Particularly, the obtained results show that in order to obtain low message error rates, a prohibitively high number of roadside units may be required. Selective message retransmission is a well-known time-domain redundancy technique, which has been also explored for vehicular communications. However, the simultaneous combination of both space- and time-domain techniques has yet to be explored. This paper presents a preliminary study of the potential benefits of such approach. Data extracted from an experimental system deployment in a Portuguese highway was used to derive a realistic error-rate model. Based on this model, simulations were carried out to assess and validate the potential benefits of such hybrid approach.